Unsolved Mysteries in NLR Biology - Lupfer, Christopher; Kanneganti, Thirumala-Devi (Frontiers in Immunology, 2013)
NOD-like receptors (NLRs) are a class of cytoplasmic pattern recognition receptors. Although most NLRs play some role in immunity, their functions range from regulating antigen presentation (NLRC5, CIITA) to pathogen/damage sensing (NLRP1, NLRP3, NLRC1/2, NLRC4) to suppression or modulation of inflammation (NLRC3, NLRP6, NLRP12, NLRX1). However, NLRP2, NLRP5 and NLRP7 are also involved in non-immune pathways such as embryonic development. In this review, we highlight some of the least well-understood aspects of NLRs, including the mechanisms by which they sense pathogens or damage. NLRP3 recognizes a diverse range of stimuli and numerous publications have presented potential unifying models for NLRP3 activation, but no single mechanism proposed thus far appears to account for all possible NLRP3 activators. Additionally, NLRC3, NLRP12 and NLRP6 inhibit NF-κB activation, but whether direct ligand sensing is a requirement for this function is not known. Herein, we review the various mechanisms of sensing and activation proposed for NLRP3 and other inflammasome activators. We also discuss the role of NLRC3, NLRP6, NLRP12 and NLRX1 as inhibitors and how they are activated and function in their roles to limit inflammation. Finally, we present an overview of the emerging roles that NLRP2, NLRP5 and NLRP7 play during embryonic development and postulate on the potential pathways involved.